The interplay between peer rejection and acceptance in preadolescence and early adolescence, serotonin transporter gene, and antisocial behavior in late adolescence: The TRAILS study - Kretschmer, Tina; Sentse, Miranda; Dijkstra, Jan Kornelis; Veenstra, René (Merrill-Palmer Quarterly-Journal of Developmental Psychology, 2014)
Gene-environment studies on adolescents' peer contexts are important for understanding the interplay between biological and social antecedents of adolescent psychopathology. To this end, this study examined the roles of serotonin transporter (5-HTTLPR) and preadolescent and early adolescent peer rejection and acceptance, as well as the interaction between genotype and environment as predictors of antisocial behavior. Longitudinal data from TRAILS (TRacking Adolescents' Individual Lives Survey), a Dutch cohort study into adolescent development that includes peer reports of rejection and acceptance assessed at 11.1 and 13.6 years and self-reported antisocial behavior at 19.1 years was used. The interaction between 5-HTTLPR and preadolescent peer rejection predicted antisocial behavior with carriers of the 5-HTTLPR short-short variant most strongly affected. No main or interaction effects were found for early adolescent rejection or interactions involving peer acceptance. Our results extend the gene- environment interaction literature by focusing on peer relationship experiences. © 2014 by Wayne State University Press, Detroit, MI 48201.
CRIS-Team Scopus Importer:2025-03-19